ASSESSMENT OF RENAL AND HEPATIC DYSFUNCTION AMONG TYPHOID FEVER PATIENTS IN BINGHAM UNIVERSITY TEACHING HOSPITAL, JOS, NIGERIA: A RETROSPECTIVE STUDY - Rotimi, Johnson Ojo; Ifeoluwapo, Modupeoluwa Ogunfowokan (FUDMA Journal of Sciences, 2025)
Typhoid fever-induced organ dysfunction contributes greatly to high morbidity and mortality associated with the disease. It is crucial to monitor all affected organs during treatment to improve patients’ survival. This retrospective study was conducted to evaluate the impact of typhoid fever on hepatic and renal functions among patients who attended Bingham University Teaching Hospital between 2019 and 2020. Records of 300 patients comprising 150 confirmed typhoid cases through widal test and blood culture, and 150 healthy controls were analysed. Results showed that typhoid fever resulted in severe anaemia, elevated serum liver enzymes and thrombocytopenia, however, significant alterations were more severe in male patients compared to females. Significant reduction in serum glucose levels, total white blood cell and differential white blood counts except lymphocyte counts were observed in typhoid fever patients. Although there was non-significant decrease in serum albumin and total protein of the patients, gender-specific analysis revealed a significant increase in serum albumin among female patients in contrast to male patients that exhibited a significant decrease in serum albumin. There were no significant differences in renal function parameters between the patient and the control except serum urea. In conclusion, hepatic dysfunction, severe anaemia and thrombocytopenia are strongly associated with typhoid fever in this population with the severity more pronounced among male patients compared to females, while renal impairment is relatively uncommon. It is advisable that patients in this area undergo liver and kidney function assessment in addition to their treatment to facilitate early detection of typhoid-induced hepatic and renal damage.
Keywords: Typhoid fever; Salmonella typhi; Liver dysfunction; Kidney dysfunction; sanitary infrastructure